Continuous delivery with Docker and Jenkins : create secure applications by building complete CI/CD pipelines - Leszko, Rafał (Packt Publishing, 2022)
Create a complete continuous delivery process using modern DevOps tools such as Docker, Jenkins, Kubernetes, Ansible, Terraform, and many more Key Features Build reliable and secure applications using Docker containers Create a highly available environment to scale Jenkins and your services using Kubernetes Automate your release process end-to-end Book Description This updated third edition of Continuous Delivery with Docker and Jenkins will explain the advantages of combining Jenkins and Docker to improve the continuous integration and delivery process of app development. You'll start by setting up a Docker server and configuring Jenkins on it. Next, you'll discover steps for building applications and microservices on Dockerfiles and integrating them with Jenkins using continuous delivery processes such as continuous integration, automated acceptance testing, configuration management, and Infrastructure as Code. Moving ahead, you'll learn how to ensure quick application deployment with Docker containers, along with scaling Jenkins using Kubernetes. Later, you'll explore how to deploy applications using Docker images and test them with Jenkins. Toward the concluding chapters, the book will focus on missing parts of the CD pipeline, such as the environments and infrastructure, application versioning, and non-functional testing. By the end of this continuous integration and continuous delivery book, you'll have gained the skills you need to enhance the DevOps workflow by integrating the functionalities of Docker and Jenkins. What you will learn Grasp Docker fundamentals and dockerize applications for the CD process Understand how to use Jenkins on-premises and in the cloud Scale a pool of Docker servers using Kubernetes Write acceptance tests using Cucumber Run tests in the Docker ecosystem using Jenkins Provision your servers and infrastructure using Ansible and Terraform Publish a built Docker image to a Docker registry Deploy cycles of Jenkins pipelines using community best practices Who this book is for The book is for DevOps engineers, system administrators, Docker professionals, or anyone who wants to explore the power of working with Docker and Jenkins together. No prior knowledge of DevOps is required to get started.